Volume- vs. rate-based tube feeding in burn patients: A case-control study. Issue 4 (October 2018) - Sheckter, Clifford C.; Rochlin, Danielle H.; Moshrefi, Shawn; Schenone, Maaike; Vargas, Vina; Sproul, Jill; Karanas, Yvonne L.
Highlights: Volume-based is superior to rate-based tube feeds in optimizing nutritional goals. A maximum rate and checking residuals ensure the safety of volume-based feeds. The most common reason for pausing tube feeds is fasting before an operation. Abstract: Background: Proper nutrition is critical in healing burn wounds. Tube feeding is routinely employed to help meet nutritional goals; however, the complexities of burn care frequently involve pausing feeds. Volume-based tube feeding delivers a 24-h goal volume compared to administering a fixed hourly rate. This study aims to assess whether volume-based tube feeding is superior to traditional rate-based tube feeding at meeting nutritional goals. Methods: Starting in January 2016, a single burn center implemented a volume-based tube feeding protocol. All patients for the calendar year 2016 who required tube feeds for at least 5 continuous days were compared to all patients from the prior calendar year 2015. Demographics, burn characteristics, and tube feeding details were compared with univariable analysis. Daily tube feed goals were the primary outcome and length of stay was assessed as a secondary outcome; both were evaluated with multivariable analysis using linear modeling. Results: Thirty patients met study criteria. The cohort was 30.0% female and 93.3% were flame burns, with a mean age of 44.2 years and mean total body surface area (TBSA) of 30.6%. All patients suffered 3rd degree burns. Pausing tube feeds for fasting before an operation was the most common reason feeds were held accounting for 33.7% of all held days. Volume-based tube feeding was the only independent predictor of increasing tube feed goals with an average goal met of 91.4% vs. 74.1%, (linear coefficient 10.05, 95% CI 4.49–15.61, p-value 0.001). Tube feed hours held was the only independent predictor of lower tube feed goals (linear coefficient −5.52, 95% CI −7.73–−3.31, p-value < 0.001). Volume-based tube feeding was not associated with a significant difference in length of stay after controlling for covariates. Rate-based feeds showed an adjusted mean stay of 33.6 (SD 7.5) days vs. 36.3 (SD 11.1) days for volume-based feeds (linear coefficient 0.84, 95% CI −13.6–15.2, p = 0.905). Conclusions: Volume-based tube feeding was superior to rate-based tube feeding in maximizing daily nutritional goals. Perioperative care was the most common reason for holding tube feeding. Additional studies are needed to assess whether volume-based feeding is associated with improved clinical outcomes.